HARVESTER PRODUCTIVITY AND COSTS IN CLEAR CUTTING Pinus taeda STANDS UNDER DIFFERENT MANAGEMENT REGIMES - Stadler, Juliano Araujo; Lopes, Eduardo da Silva; Rodrigues, Carla Krulikowski; de Oliveira, Felipe Martins; Diniz, Carlos Cézar Cavassin (Floresta, 2022)
The increased demand for several forest products makes it necessary to apply different management regimes in forest stands, which may influence the wood harvesting operations. This study aimed to evaluate the effect of average individual tree volumes obtained through different management regimes on harvester productivity and costs, thereby enabling to generate information for forest managers. The study was carried out in three Pinus taeda L. stands under clear cutting with different average individual tree volumes (AIV): I (0.367 m3); II (0.582 m3); and III (0.766 m3). Working cycle times, productivity per productive machine hour, energy yield and production costs were obtained by a time and motion study, in which the average values obtained were compared by the Tukey-Kramer test (α ≤ 0.05). The work elements of the harvester’s work cycles were affected by forest management regimes, mainly the movement and the processing, with significant statistical difference between stands, but no difference between total working cycle times. The management regime applied to forest stands influenced the spacing and whole trunk volume which consequently increased the average productivity of the machine from 36.8 to 74.1 m³ per productive machine hour in treatments I and III, respectively, and reduced production costs by 50%. The forest management regimes influenced the clear-cutting operation with harvester.